2002
DOI: 10.1093/oxrep/18.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Universities and Fundamental Research: Reflections on the Growth of University-Industry Partnerships

Abstract: The recent rise in university-industry partnerships has stimulated an important public policy debate regarding how these relationships affect fundamental research. In this paper, we examine the antecedents and consequences of policies to promote university-industry alliances. Although the preliminary evidence appears to suggest that these partnerships have not had a deleterious effect on the quantity and quality of basic research, some legitimate concerns have been raised about these activities that require ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(102 citation statements)
references
References 34 publications
(20 reference statements)
1
98
0
3
Order By: Relevance
“…This is reasonable since these academics are also entrepreneurs at the same time and consecutively practically business oriented. This finding is consistent with authors that found a positive relationship between industry-funding and applied research (Gulbrandsen & Smeby, 2005;Poyago-Theotoky et al, 2002;Rahm, 1994;Van Looy et al, 2004). Our results also reveal that academic entrepreneurs after they establish their spin-off companies employ more funds for applied research then before which coincides with more applied research conducted after the spin-off creation.…”
Section: Resultssupporting
confidence: 92%
“…This is reasonable since these academics are also entrepreneurs at the same time and consecutively practically business oriented. This finding is consistent with authors that found a positive relationship between industry-funding and applied research (Gulbrandsen & Smeby, 2005;Poyago-Theotoky et al, 2002;Rahm, 1994;Van Looy et al, 2004). Our results also reveal that academic entrepreneurs after they establish their spin-off companies employ more funds for applied research then before which coincides with more applied research conducted after the spin-off creation.…”
Section: Resultssupporting
confidence: 92%
“…[140] These type of research are frequently happens at the other countries, [141,142] but low numbers in this country, Malaysia. In industries, research and development are frequently happens in the inside, but there are not many of them convert the research into a publication.…”
Section: Discussion and Recommendationmentioning
confidence: 99%
“…Therefore, projects of this nature tend to involve applied research instead of fundamental research, as argued by Poyago-Theotoky et al (2002). The considerable financial resources which accompany licensing also strengthen the incentive to focus on applied research.…”
Section: Uirs' Effects On Universitiesmentioning
confidence: 99%
“…In particular, universities interact with DBFs through joint research projects in which knowledge is mutually exchanged. Mixed teams of university and LDF researchers working on a joint research project are unlikely to be observed in reality (Poyago-Theotoky et al, 2002). Therefore, we designed the interaction between universities and LDFs in a twofold way as licensing or sponsoring relations.…”
Section: University-industry Relationshipsmentioning
confidence: 99%